Nanosecond imaging and emission spectroscopy of argon streamer micro-discharge developing in coplanar surface DBD. (29th May 2018) - Šimek, M; Ambrico, P F; Hoder, T; Prukner, V; Dilecce, G; De Benedictis, S; Babický, V
Abstract: Time-resolved microscopic ICCD images, emission waveforms and spectra of triggered single-surface coplanar dielectric barrier micro-discharges were acquired with nanosecond time resolution. The micro-discharges were produced in pure argon by applying periodic high-voltage waveforms to a pair of embedded metallic electrodes at atmospheric pressure, and microscopic images of single micro-discharge events complemented with spectrally resolved emission were acquired with a time resolution of a few nanoseconds. Due to the low jitter of the micro-discharge onset with respect to the high-voltage pulse, we succeeded in separating the very weak emission produced during the course of streamer formation from the emission produced during the transition between the streamer and the subsequent transient glow phase. We identified the characteristic spectrometric signatures of the transition between the streamer and glow phases by analysing the lines belonging to the Ar(3s 2 3p 5 4p → 3s 2 3p 5 4s) multiplet. By linking optical and electrical measurements, we estimated the electron density with a high temporal resolution. The electron densities of the streamer discharge, determined spectroscopically, were in the range of 10 19 –10 20 m −3, while an estimate of 10 21 m −3 was obtained using macroscopic electrical analysis combined with ICCD imaging. The evolution of selected population ratios of 2p levels during streamer evolution was determined for the first time, and this may be used in the future for advanced streamer diagnostics.